CLUSTERING OF DOCUMENT COLLECTIONS BASED ON THE ADAPTIVE SELF-ORGANIZING NEURAL NETWORK - Bodianskiy, Ye. V.; Volkova, V. V.; Yegorov, A. S. (Radio Electronics, Computer Science, Control, 2008)
In this paper the text document clustering method based on an adaptive self-organizing neural network is proposed. The adaptive self-organizing neural network allows to find cluster centroids in real time. The network is tuning using self-learning recursive algorithm that is the generalization of Kohonen learning rule. This neural network can be used in clusterization of text documents in conditions of overlapping classes.